Influence of cysteamine supplementation during in vitro culture of early stage caprine embryos on blastocyst production - KHARCHE, S D; AGRAWAL, S; PATHAK, J; SIKARWAR, A K S; GANGAWAR, CHETNA; RANJAN, RAVI; GOEL, A K; JINDAL, S K; AGARWAL, S K (The Indian Journal of Animal Sciences, 2016)
The objective of this study was to evaluate the effect of cysteamine supplementation on embryo development in mCR2 media. The COCs (1251) were matured in TCM–199 medium containing FSH (5µg/ml), LH (10µg/ml), follicular fluid (10%), FBS (10%) with 3 mg/ml BSA for 27h at 38.5°C and 5% CO2 in an incubator. Matured oocytes were co-cultured with 1×106 spermatozoa/ml collected from a Sirohi buck in fertTALP (10% FBS+ 4mg/ml BSA and 10 µg/ml heparin) for 18 h in incubation. After 18 h of sperm-oocytes, co-incubation of oocytes with sperms were washed in embryo development medium to remove sperm cells adhered to zonapellucida. Presumptive zygotes (1,171) were selected and randomly divided into 2 groups. Group 1, the presumptive zygotes (610) were cultured in mCR2aa as a control for 12 days. Group 2, the presumptive zygotes (561) were culture in mCR2aa medium supplemented with 100 µM cysteamine for 10 days. The percentage of cleavage, morula, and blastocyst production in groups 1 and 2 were 36.39% and 31.71% (cleavage); 21.62% and 30.89% (morula); 4.95% and 8.98% (blastocyst) respectively. In conclusion, results indicated that the addition of cysteamine to the IVC medium stimulates caprine embryo development and blastocyst production.